Wykładniki predykacji w języku polskim i francuskim - Kaliska, Agnieszka K. (Wydział Neofilologii UAM w Poznaniu, 2016)
The aim of the present study is to compare different forms of predicate that can be realized in French and in Polish: verbs, nouns, adjectives and adverbs. The extra-linguistic reality is similar to a large extent, still the forms of stating about the reality in these two languages can be different. This study aims to determine to what extent Polish and French differ from one another as far as the surface structure level is concerned. It turns out that one may not speak of complete adherence of both systems especially due to the language-specific properties that influence the expression level, such as definiteness, nominalization, case-marking, aspect and/or Aktionsart categories and marking, voice and valency. A predicate, being basically the same, may be then expressed through different ways, which in turn allows to individuate structure-specific meaning components.
Keywords: predicate; verb; nominalization; predicative adjective; Polish; French